Physical Activity in the Elderly and Orthopaedic Surgery - Papalia, Rocco; Denaro, Vincenzo; Pigozzi, Fabio; Fossati, Chiara (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Old age is increasingly becoming the focus of research and development in Europe. Concerning orthopaedics and sports medicine, the elderly especially are considered as frail patients who need support to maintain the health of their musculoskeletal systems. For this reason, several interventions regarding physical activity have been investigated in recent years in order to understand whether some programs of physical activity are better than others as conservative treatments for degenerative musculoskeletal pathologies (i.e., osteoarthritis, rotator cuff arthropathy, and lower back pain). Furthermore, several investigations have been carried out to understand the best preoperative and postoperative protocols of physical activity to improve the results of orthopaedic surgery. The aim of this Special Issue was to collect the updated evidence concerning these topics in the form of a collection of systematic reviews of the literature.